Textile visionaries : innovation and sustainability in textile design - Quinn, Bradley (London : Laurence King Publishing, 2013)
Technologized textiles and sustainable fabrics are among the most innovative designed today, and together they are driving the rest of the industry dramatically forward. Many designers are now integrating hi-tech fabrics, such as protective and impact-resistant textiles, or cellulose fabrics, with groundbreaking results. Embracing new processes such as biomimicry, they bridge the gap between art, design, technology, and sustainability more than any other material. This book shows how the development of fabrics today is immersed in technology, sustainability, and innovation.
Includes index.
boek